Noroviruses are highly infectious but there is strong variation in host susceptibility and virus pathogenicity - Teunis, Peter F.M.; Le Guyader, Françoise S.; Liu, Pengbo; Ollivier, Joanna; Moe, Christine L. (Epidemics, 2020)
•Noroviruses have been studied in human challenge experiments, to estimate infectivity.•We have shown how norovirus infectivity can also be estimated from qualifying outbreaks.•This study combines challenge studies and natural experiments to quantify infectivity.•Secretor negatives are clearly protected against norovirus infection, across all studied variants.•GII viruses appear less infectious than GI, but there is strong variation within genogroups. Noroviruses are a major public health concern: their high infectivity and environmental persistence have been documented in several studies. Genetic sequencing shows that noroviruses are highly variable, and exhibit rapid evolution. A few human challenge studies have been performed with norovirus, leading to estimates of their infectivity. However, such incidental estimates do not provide insight into the biological variation of the virus and the interaction with its human host. To study the variation in infectivity and pathogenicity of norovirus, multiple challenge studies must be analysed jointly, to compare their differences and describe how virus infectivity and host susceptibility vary. Since challenge studies can only provide a small sample of the diversity in the natural norovirus population, outbreaks should be exploited as an additional source of information. The present study shows how challenge studies and ‘natural experiments’ can be combined in a multilevel dose response framework. Infectivity and pathogenicity are analysed by secretor status as a host factor, and genogroup as a pathogen factor. Infectivity, characterized as the estimated mean infection risk when exposed to 1 genomic copy (qPCR unit)is 0.28 for GI norovirus, and 0.076 for GII virus, both in Se+ subjects. The corresponding risks of acute enteric illness are somewhat lower, about 0.2 (GI) and 0.035 (GII), in outbreaks. Se− subjects are protected, with substantially lower risks of infection (0.00007 and 0.015 at a dose of 1 GC of GI and GII virus, respectively). The present study shows there is considerable variability in risk of infection and especially risk of acute symptoms following infection with norovirus. These challenge and outbreak data consistently indicate high infectivity among secretor positives and protection in secretor negatives.